Droplet digital PCR revealed high concordance between primary tumors and lymph node metastases in multiplex screening of KRAS mutations in colorectal cancer - Vanova, Barbora; Kalman, Michal; Jasek, Karin; Kasubova, Ivana; Burjanivova, Tatiana; Farkasova, Anna; Kruzliak, Peter; Busselberg, Dietrich; Plank, Lukas; Lasabova, Zora (Clinical and experimental medicine, 2019)
The proto-oncogene KRAS belongs among the most frequently mutated genes in all types of cancer and is also very important oncogene related to colorectal tumors. The detection of mutations in this gene in primary tumor is a predictive biomarker for the anti-EGFR therapy in metastatic CRC (mCRC); however, the patients with wild-type KRAS can also show resistance to the personalized medicine. The droplet-based digital PCR technology has improved the analytical sensitivity of the mutations detection, which led us to the idea about the optimization of this approach for KRAS testing. In this study, we report the application of ddPCR technology in order to analyze the presence of KRAS mutations in primary tumor and matched metastasis in lymph nodes (LNs) from patients with mCRC and address the question, whether the improvement in the detection method can lower the discrepancies of KRAS mutations detection between the primary tumor and regional LNs. Genomic DNA with wtKRAS and commercial DNA with mtKRAS (G12D) were used to set up the ddPCR reaction. Formalin-fixed paraffin-embedded tissues from primary tumor and positive lymph node from 31 patients with mCRC were analyzed using ddPCR and Sanger sequencing. KRAS status of primary tumors was known; however, the mutation status of lymph nodes was not detected previously. From 31 samples of primary tumors, our results corresponded to results from IVD kit in 30 cases. For one patient, ddPCR detected KRAS mutation in comparison with negative result of the IVD kit. In the samples of metastatic infiltrated LNs, ddPCR detected 16 samples as a WT KRAS and 15 lymph nodes showed positivity for KRAS mutation, whereby Sanger sequencing found KRAS mutations in 8 cases only. We also found two cases where genetic conditions of KRAS gene differed between primary tumor and infiltrated lymph node, both "low-grade" adenocarcinoma. Our study approved that ddPCR method is adequate technique with high sensitivity and in the future may be used as a diagnostic tool for evaluation of KRAS mutations, especially in infiltrated LNs of patients with mCRC.
Keywords: polymerázová řetězová reakce; lidé; mutantní proteiny; senzitivita a specificita; lymfatické uzliny; Female; Sensitivity and Specificity; Proto-Oncogene Mas; molekulární patologie; Colorectal cancer; Humans; Polymerase Chain Reaction; Colon; KRAS mutation testing; Mutant Proteins; protoonkogen Mas; Lymph nodes; Pathology, Molecular; mužské pohlaví; kolon; kolorektální nádory; Lymph Nodes; ženské pohlaví; Droplet digital PCR; Colorectal Neoplasms; protoonkogenní proteiny p21(ras); Male; Aged; Proto-Oncogene Proteins p21(ras); senioři